Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 208852 by Tawa11 last updated on 25/Jun/24

Answered by Frix last updated on 25/Jun/24

3^(−3(x^2 −x)) =x^2 −x ⇒ x^2 −x>0 ⇔ x<0∨x>1  t=x^2 −x ⇔ x=(1/2)±((√(4t+1))/2)  3^(−3t) =t     [ _(but let′s continue)^(It′s obvious to me that t=(1/3)) ]  −3tln 3 =ln t  t=e^(−u)   −3e^(−u) ln 3 =−u  ue^u =3ln 3  u=ln 3  t=(1/3)  x=((3±(√(21)))/6)

33(x2x)=x2xx2x>0x<0x>1t=x2xx=12±4t+1233t=t[butletscontinueItsobvioustomethatt=13]3tln3=lntt=eu3euln3=uueu=3ln3u=ln3t=13x=3±216

Commented by Tawa11 last updated on 25/Jun/24

Thank you sir.

Thankyousir.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com